Implementation Of Value Engineering Using Analytical Hierarchy Process (Ahp) (Case Study: Flyover Construction Project Of Jpl 64 Km 38+897 Across Surabaya – Solo) - Naufal Akbar Muzaky; Fajar Sri Handayani; Ary Setyawan (Sustainable Civil Building Management and Engineering Journal, 2024)
The development of infrastructure development in Indonesia is being intensively carried out by the government to meet the needs of the community. Infrastructure development is often faced with various obstacles that can disrupt the project. To ensure the sustainability of the project, it is necessary to apply Value Engineering to identify opportunities for cost savings and solve problems so as to get maximum value without reducing project quality. The purpose of the research is to analyze the structure, determine the alternative, types and construction methods chosen to make the project cost efficient. Value Engineering is applied to the foundation and deck slab work of the Fly Over Replacement Construction Project JPL 64 Km 38-897 Lintas Surabaya-Solo using the AHP method with the help of expert choice. Based on the results of the Value Engineering analysis, an alternative bore pile d-120 foundation was obtained in the foundation work and a change in the cantilever elbow support method in the deck slab work. The cost efficiency results obtained after Value Engineering amounted to Rp15,108,214,225 or 10%.